A hydrologic approach to environmental golf and hazard design within the Wildcat Creek Watershed - Clark, Jeffrey (Kansas State University, 2012)
The City of Manhattan, Kansas is looking for possible solutions to mitigate flooding along Wildcat Creek within the Wildcat Creek Watershed. Recent flooding has caused substantial property damage. The project presented here brings recreation into the community by designing a golf course in a location along Wildcat Creek that addresses flooding issues, increases infiltration, and improves water quality. The golf industry has a long way to go to become more sustainable. The world is facing many challenges related to water and hydrology. Much of the opposition towards the golf industry is because critics see it as environmentally unfriendly. Golf has the potential to become a catalyst for change in the way we design and develop the landscape around us. The golf industry can become a leader in sustainable design while taking on hydrological concerns within the community. This project demonstrates the application of a golf course to help mitigate flooding along Wildcat Creek with the use of vulnerability and suitability analysis as a guide to site selection. This method of analysis illustrates the process of identifying and protecting areas vulnerable to degradation by designing a golf course in a suitable location to utilize water hazards to store flood water, provide more floodplain access to effectively increase infiltration capacity, reduce runoff rates, and improve water quality. The report explains the relationship between golf course design and environmental practices as they relate to hydrology on a theoretical site in Manhattan, Kansas. By integrating golf course design theory and environmentally sound stormwater management practices, water hazards on the golf course can become the fundamental elements used in strategizing the design of the golf course. A conceptual plan was created to maximize the infiltration capacity of the site as well as allow increased floodplain access, and provide a place to store flood water. A golf course can then be properly sited and designed hydrologically around the use of water hazards to help reduce flooding and improve water quality within the watershed.
Keywords: Wildcat Creek Watershed; Golf course; Flooding; Stormwater management; Water hazards; Best management practices; Landscape Architecture (0390)